Dissolution of BiVO4 Photoanodes Revealed by Time-Resolved Measurements under Photoelectrochemical Conditions - Zhang, Siyuan; Rohloff, Martin; Kasian, Olga; Mingers, Andrea M.; Mayrhofer, Karl; Fischer, Anna; Scheu, Christina; Cherevko, Serhiy (Journal of Physical Chemistry C, 2019)
Photocorrosion imposes a fundamental limit to the longevity of devices that harvest energy from photons. As one of the best performing electrode materials for photoelectrochemical water oxidation reaction, BiVO4 undergoes photocorrosion with various postulated mechanisms under debate. We present time-resolved dissolution measurements to advance the mechanistic understanding, enabled by the recent development in illuminated scanning flow cell coupled to inductively coupled plasma mass spectrometry. The contact dissolution of predominantly V was distinguished from the stoichiometric photoelectrochemical dissolution of Bi and V. The citrate electrolyte was utilized to form soluble complexes with dissolved Bi and to act as hole scavengers that provide photocurrents at a wide range of potentials. The photoelectrochemical dissolution rates remain similar between 0.4 and 1.6 V vs reversible hydrogen electrode and become lower at the open circuit potential, 0.2 V. The time-resolved measurements support oxidation of Bi(III) by photogenerated holes as the main mechanism for photocorrosion.
CRIS-Team Scopus Importer:2019-10-15